Exploring the Role of Artificial Intelligence in Eradicating Poverty and Enhancing Global Security in South Africa: A Regulatory Perspective - Chitimira, Howard; Munedzi, Sharon (EuroEconomica, 2024)
This article analyses the potential role of artificial intelligence (AI) in the eradication of poverty and the promotion of global security in the South African context. It investigates whether AI could be utilised to alleviate poverty and enhance global security in various sectors such as healthcare, agriculture, education, disaster management, environmental sustainability and humanitarian assistance. The article further explores the possible benefits of AI in creating new job opportunities, increasing economic growth, improving healthcare, reducing agricultural challenges, enhancing access to education, monitoring and mitigating the impact of climate change and providing aid to refugees and other displaced persons in South Africa. It is also noted that the use of AI is often criticised for algorithmic bias, discrimination challenges, privacy violations and cybersecurity challenges. The article also acknowledges various challenges involved in the regulation of AI without a uniform legal framework and/or without a coordinated approach to AI regulation globally. In this regard, it is submitted that AI should be carefully regulated and employed for the benefit of the people without affecting their human rights and other related rights. Lastly, the article scrutinises the role of AI in combating poverty and enhancing global security so as to expose the potential risks, disadvantages and advantages of AI in South Africa.